2020
DOI: 10.1080/07853890.2020.1814962
|View full text |Cite
|
Sign up to set email alerts
|

Important role of microglia in HIV-1 associated neurocognitive disorders and the molecular pathways implicated in its pathogenesis

Abstract: The development of effective combined anti-retroviral therapy (cART) led to a significant reduction in the death rate associated with human immunodeficiency virus type 1 (HIV-1) infection. However, recent studies indicate that considerably more than 50% of all HIV-1 infected patients develop HIV-1-associated neurocognitive disorder (HAND). Microglia are the foremost cells infected by HIV-1 in the central nervous system (CNS), and so, are also likely to contribute to the neurotoxicity observed in HAND. The acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 213 publications
(321 reference statements)
4
77
0
Order By: Relevance
“…Apart from higher number of PC in the WM, we also observed nodular lesions formed by microglia nodules (MN) that were more prevalent in the WM than in the GM of the SIV-infected brain (Zhang et al, 2019), suggesting involvement of microglia in virus-induced WM injury as reported by many other studies (Borrajo et al, 2021;Wallet et al, 2019). The formation of MN in normal appearing WM was also observed in early stage of MS, which occurred before T-cell infiltration (Singh et al, 2013).…”
Section: Introductionsupporting
confidence: 80%
“…Apart from higher number of PC in the WM, we also observed nodular lesions formed by microglia nodules (MN) that were more prevalent in the WM than in the GM of the SIV-infected brain (Zhang et al, 2019), suggesting involvement of microglia in virus-induced WM injury as reported by many other studies (Borrajo et al, 2021;Wallet et al, 2019). The formation of MN in normal appearing WM was also observed in early stage of MS, which occurred before T-cell infiltration (Singh et al, 2013).…”
Section: Introductionsupporting
confidence: 80%
“…The increased and chronic inflammatory status in the brain may contribute to neurodegeneration due to increased neuronal cell death and reduced neurogenesis, reduced remodeling and irreparable damage to the neuronal network, resulting in an enhanced or accelerated brain aging process. In the context of microglia and viral infection, most research has been done in HIV, where the association has been shown for neurocognitive decline [ 127 , 128 , 228 , 246 ]. However, there is little information available about the cellular and molecular mechanisms that contribute to or influence the chronic HIV infection and corresponding involvement of microglia, which requires more future research.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed cellular and molecular mechanisms responsible for HAND have still to be elucidated [ 124 , 125 ]. However, chronic HIV infection results in corresponding neuroinflammation with activation of microglia and astrocytes [ 126 , 127 , 128 ]. There is also increasing evidence that there is production and deposition of beta-amyloid peptide, similar to Alzheimer’s disease [ 129 , 130 ].…”
Section: Virus Infection In the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…memory and executive functions [8]. Because HIV replication in the CNS occurs principally in microglia (the resident macrophage-type cells), is thought that both, direct effects of viral proteins, and indirect effects mediated by microglia activation and secretion of neurotoxic products can contribute to neuronal damage [9,10]. However, the causes for such neurological dysfunctions are diverse and will be discussed in this review.…”
Section: Introductionmentioning
confidence: 99%